(untitled) (Revista Electrónica REDINE, 2024)
Information theory and entropy are related in the context of management and information management in organizations. In information theory, entropy is used as a measure of the uncertainty or disorder in a set of messages. The amount of information needed to reduce that uncertainty will depend on the way the message is organized; from there, part of the usefulness of information theory in managerial praxis emerges, because efficient communication will seek to reduce entropy and maximize useful and relevant information for managerial decision-making. The purpose of the essay is to identify entropy in information theory as a communication barrier for managerial praxis. As theoretical references we have Clausius (1865), creator of the term entropy, Shannon and Weaver (1948), precursors of information theory or mathematical theory of communication, Bertalanffy (1958) with general systems theory, Katz and Kahn (1986) with its contributions to organizations as systems. After a documentary review of the aforementioned theories, it is concluded that, communication barriers and the lack of clarity or distortion of messages are known within information theory as entropic elements, which can make understanding and accurate interpretation difficult of information, and in turn affect the decision-making process based on incomplete or incorrect information, disturbing management praxis